Current provision and challenges for paediatric radiotherapy in Romania: A survey by the SIOP Europe QUARTET project - Andrada Turcas; Sarah M. Kelly; Anne Blondeel; Monica Chirila; Dana M. Cernea; Henry C. Mandeville (EJC Paediatric Oncology, 2023)
Introduction: Significant differences in outcome and survivorship in childhood cancer still exist across Europe, with poorer results in eastern regions. We aimed to map the provision of paediatric radiotherapy in Romania, identifying the key future requirements and main challenges. Methods: An online survey supported by SIOP Europe was distributed to all 33 (13 public, 20 private) radiotherapy departments operating across Romania. The questionnaire contained 22 open-ended and multiple-choice questions, exploring resources, clinical trial participation, patient referral practice, and Radiotherapy Quality Assurance (RTQA). Results: Nineteen centres (58%) responded to the survey, ten of which treat children and seven having designated radiation oncologists for paediatric patients. While access to advanced photon techniques is high (16/19 with IMRT/IMAT), only six centres report availability of general anaesthesia. Participants agree that challenges include a lack of national/regional specialised paediatric radiotherapy centres, limited access to mentors or training opportunities, and availability of robust multidisciplinary tumour boards. Only one centre reports participating in paediatric radiotherapy clinical trials; likely attributable to a lack of national trial infrastructure and poor local engagement. Physicians in 16 centres refer children for proton therapy but find the long waiting time and laborious paperwork difficult. Sixteen responders considered paediatric RTQA essential; agreeing that a (inter)national RTQA programme is needed and would benefit patients. Conclusions: While advanced radiotherapy techniques are widely available for children in Romania, the lack of centralised and harmonised practice, scarce training opportunities, underdeveloped clinical trial infrastructure, and laborious proton referral process highlighted by the survey, describe a complex landscape. Future improvements are required, including establishing strategic national and international multi-stakeholder collaborations.